Salivary Gland Adenocarcinoma Metastasis to the Brain in an Adult: A Case Report - Pawar, Samadhan; Borde, Chaitanya; Patil, Atul; Nagarkar, Rajnish (Asian Journal of Medical Radiological Research, 2019)
Salivary gland malignancies are a heterogeneous group of 24 tumours that have unpredictable clinical behaviours and predilections for metastasis. Although salivary gland metastasis is an uncommon finding, it comprises of only 1-6% of all malignancies in the head and neck region. It is a common clinical practice to surgically resect salivary gland tumours which is followed by radiation to the tumour bed. The overall combination of chemo-radiation approaches has helped clinically control the primary disease. However, many patients have presented with systemic metastasis including the brain. Long-term follow-up of such patients is an added value for radiologist and oncologists. We report an unusual case of salivary gland adenocarcinoma metastasis to the brain in an adult with a key focus on its radiological perspective.